2021
DOI: 10.3389/fnmol.2021.650338
|View full text |Cite
|
Sign up to set email alerts
|

CREB3L2 Modulates Nerve Growth Factor-Induced Cell Differentiation

Abstract: Nerve growth factor (NGF) stimulates numerous cellular physiological processes, including growth, differentiation, and survival, and maintains the phenotype of several neuronal types. Most of these NGF-induced processes require adaptation of the secretory pathway since they involve extensive remodeling of membranes and protein redistribution along newly formed neuritic processes. CREB3 transcription factors have emerged as signaling hubs for the regulation of numerous genes involved in the secretory pathway an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…CREB1 plays a role in cell proliferation, myogenic differentiation and other related pathways [ 20 ]. CREB3 is involved in embryonic development and the differentiation of other tissues and organs, such as osteoblast differentiation [ 21 ]. In order to visualize the downstream signaling genes regulated by these two TFs, we present the regulatory network centered on TFs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CREB1 plays a role in cell proliferation, myogenic differentiation and other related pathways [ 20 ]. CREB3 is involved in embryonic development and the differentiation of other tissues and organs, such as osteoblast differentiation [ 21 ]. In order to visualize the downstream signaling genes regulated by these two TFs, we present the regulatory network centered on TFs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, however, we found that the expression of N-terminal domains of CREB3L2 was reduced in GECs and PIE after GMSC sheet treatment both in vitro and in vivo. In a previous study, as a crucial downstream effector of the NGF activation pathway, the CREB3L2 protein negatively regulates neurite outgrowth (Sampieri et al 2021). The modulatory effects are similar to our results for overexpressing and knocking down CREB3L2, indicating that CREB3L2 may act as negative feedback on the formation of HDs.…”
Section: Discussionmentioning
confidence: 98%
“…From a mechanical perspective, the C-terminal CREB3L2 binds to Patched-1 receptors on developing axons with Shh ligands, facilitating axon growth 58 . Additional findings suggest that CREB3L2 plays a significant regulatory role in modulating neuron differentiation induced by nerve growth factor, as well as oligodendrocyte maturation and apoptosis [59][60][61] . In addition to the well-studied N-terminal and C-terminal fragments, another fraction of CREB3L2, the so-called BBF2H7-derived small peptide (BSP), which was a short peptide located between the S1P and S2P splice sites and a product upon RIP during ER stress, was found in many neural tissues.…”
Section: Development and Disease Progression Of The Neural Systemmentioning
confidence: 90%